Langgar Lembaga Pendidikan Islam - Pardede, Rizky Nur Zannah; Suryani, Ira; Pohan, Hafsah Winona; Nur’aini, Widya; Aldi, Dwiansyah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Langgar (prayer house) or often called mushollah. According to the 2018 KBBI, the word langgar is a small mosque that is usually used as a place of prayer or Quran recitation, but there are no Friday prayers in it. Langgar is the oldest Islamic institution in the field of education that has existed and developed in the Islamic community of our country. Langgar is an Islamic educational institution that was first established before the pesantren came into existence. Langgar has an educational element that makes up a system that includes caregivers, learners (students), goals, methods, materials, assessment. Langgar also has quite a broad position, namely helping the community solve problems in a forum and supporting the continuous learning process teaching Islam to Muslim citizens. Keywords: langgar, islamic institution